2011
DOI: 10.1007/s00198-010-1479-8
|View full text |Cite
|
Sign up to set email alerts
|

Age trends for hip geometry in Chinese men and women and the association with femoral neck fracture

Abstract: This study demonstrated thinning of the cortical shell and deterioration of the resistance to bending and SI with aging in femoral neck in Chinese men and women. SI may be a risk factor for hip fracture that is independent of BMD measurement in Chinese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
3
18
0
2
Order By: Relevance
“…It was found not only that FN-BMD was the best hip fracture predictor in males but also that NSA does not predict hip fracture independent of FN-BMD. This agrees with reports by some authors 16,18 but is in contrast to the findings of Alonso et al 14 and the majority of reports in the literature about NSA hip fracture prediction in females. 10,11,14,22,26 Concerning the independence of the ability of NSA to predict hip fracture, the contrasting results between previous studies in females 10,29 and the present one in males might be a result of a statistical weakness of the present study because of the low number of fractures in males.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was found not only that FN-BMD was the best hip fracture predictor in males but also that NSA does not predict hip fracture independent of FN-BMD. This agrees with reports by some authors 16,18 but is in contrast to the findings of Alonso et al 14 and the majority of reports in the literature about NSA hip fracture prediction in females. 10,11,14,22,26 Concerning the independence of the ability of NSA to predict hip fracture, the contrasting results between previous studies in females 10,29 and the present one in males might be a result of a statistical weakness of the present study because of the low number of fractures in males.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it may be that the negative correlation of FN-BMD with NSA leads BMD to capture some of the effects of NSA on hip fracture; thus explaining, at least partially, the disagreement between males and females regarding the independence of the ability of NSA to predict hip fracture. Zhang et al, 18 who found that NSA does not independently predict hip fracture in females thus showing a significant relationship between NSA and BMD, also seem to support this hypothesis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…FSI and HAL are also reported to change as a result of age. Zhang et al performed the first study investigating the aging trends of hip geometry [23]. After adjustment for height and weight, HAL was shown in this cross-sectional study to increase with age while FSI tended to decrease (Figures 8 and 9) [23].…”
Section: Fsi and Hal: Geometric Measurements To Predict Hip Fracturementioning
confidence: 61%
“…Thus, it is not surprising that lower FSI values appear well correlated to increased fracture incidences. Even after adjustment for BMD and HAL, FSI remains a significant predictor of hip fracture [7,23]. Similarly, HAL has been shown to be a predictor of hip fracture independent of BMD, age, height, and weight.…”
Section: Fsi and Hal: Geometric Measurements To Predict Hip Fracturementioning
confidence: 96%